Knowledge, attitude and practices of HIV post exposure prophylaxis amongst health workers in Lagos University Teaching Hospital - Ajibola, Sarah (Pan Afr Med J, 2014)
INTRODUCTION: Timely PEP after needle stick exposure to high risk body fluids can reduce the rate of occupational transmission significantly. Ignorance of this may increase the risk of seroconversion to HIV for healthcare workers. This study was conducted with the aim of demonstrating the current level of knowledge and practise of healthcare workers as regards PEP. METHODS: This was a cross-sectional study, pretested questionnaire were self administered to 372 health workers from various clinical specialties. The responses were collated and analyzed; results were presented in frequency tables. RESULTS: This study revealed a high level of awareness among the respondents as 83.3% were aware of PEP. Despite the high level of awareness, respondents still have an inadequate knowledge about PEP, only 32% of the respondents could name at least two of the recommended drugs for PEP, only 54.0% of respondents knew when to commence PEP following occupational exposure to HIV. There was a low level of practice of PEP among the respondents as only 6.3% of respondents had PEP despite occurrence of needle stick injury. CONCLUSION: This study revealed a general low level use of PEP despite the average knowledge of PEP and the favourable attitude towards HIV PEP amongst the respondents.